Untangling effects of proteins as stabilizers for foam films - Gräff, Kevin; Stock, Sebastian; Mirau, Luca; Bürger, Sabine; Braun, Larissa; Völp, Annika; Willenbacher, Norbert; von Klitzing, Regine (Frontiers in Soft Matter, 2022)
Foam film’s properties have a high impact on the properties of the macroscopic foams. This work focusses on protein stabilized foam films. The direct comparison of three different proteins with a concentration normalized to the protein surface enables to distinguish between electrostatic, steric and network stabilization effects. In order to untangle those effects, we study and compare two globular proteins (lactoglobulin, BLG, and bovine serum albumin, BSA) and a disordered, flexible protein (whole casein, CN) at low ionic strengths with varying solution pH. Image intensity measurement as a recently developed image analysis methods in this field allows to record spatially resolved disjoining pressure isotherms in a Thin Film Pressure Balance (TFPB). This reveals insights into the structure formation in inhomogeneous protein films. As a novel method we introduce tracking inhomogeneities (features) which enables the measurement of interfacial mobility and stiffness of foam films. Around the isoelectric point (IEP), Newton Black Films (NBF) form which are stable for the globular proteins while they are unstable for the disordered flexible one. This difference in film stability is explained by different characteristics of the network structures which is supported by findings in the bulk and at the surface of the respective protein solutions.